Analisis Kepribadian Sayyidah Fatimah: Membangun Karakter Islami dengan Meneladani Sosok Mulia dalam Sejarah Islam - Munawir, Munawir; Faliani, Eli; Ulya, Hanum Kholidiya (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
Exemplary in a broad sense means exemplifying something. Actions that are imitated or imitated by others, such as a person's words, attitudes, and actions. Islamic morality is a value system based on the Koran and Hadith which regulates the attitudes and patterns of human behavior on earth. It seems that moral issues need serious attention, because if we don't address them, future generations of the nation will be destroyed. Researchers have identified a very noble figure to emulate: Fatimah as-Zahra. The research method used is library research. A literature review was carried out to find out the life story of Sayyidah Fatimah, characteristics and examples of exemplary behavior in various aspects of life. From the results of this research, Fatimah as-Zahra is recognized as the woman who rules heaven because she has the characteristics of perfect honesty and trustworthiness, always being loyal and obedient to her husband. Rahmat in carrying out his duties, responsible, generous and willing to sacrifice for others, tough in facing challenges, definitely social and religious, obedient to Allah SWT, but willing to pray for others before himself. At that time she was an intelligent woman, big-hearted, generous, patient in facing problems, and persistent in her preaching. Therefore, it is very important to emulate Sayyidah Fatimah in order to strengthen your Islamic character and become a better human being.